International prescribing patterns and polypharmacy in older people with advanced chronic kidney disease: results from the European Quality study. Issue 3 (16th June 2020) - Hayward, Samantha; Hole, Barnaby; Denholm, Rachel; Duncan, Polly; Morris, James E; Fraser, Simon D S; Payne, Rupert A; Roderick, Paul; Chesnaye, Nicholas C; Wanner, Christoph; Drechsler, Christiane; Postorino, Maurizio; et al.
Abstract: Background: People with chronic kidney disease (CKD) are at high risk of polypharmacy. However, no previous study has investigated international prescribing patterns in this group. This article aims to examine prescribing and polypharmacy patterns among older people with advanced CKD across the countries involved in the European Quality (EQUAL) study. Methods: The EQUAL study is an international prospective cohort study of patients ≥65 years of age with advanced CKD. Baseline demographic, clinical and medication data were analysed and reported descriptively. Polypharmacy was defined as ≥5 medications and hyperpolypharmacy as ≥10. Univariable and multivariable linear regressions were used to determine associations between country and the number of prescribed medications. Univariable and multivariable logistic regression were used to determine associations between country and hyperpolypharmacy. Results: Of the 1317 participants from five European countries, 91% were experiencing polypharmacy and 43% were experiencing hyperpolypharmacy. Cardiovascular medications were the most prescribed medications (mean 3.5 per person). There were international differences in prescribing, with significantly greater hyperpolypharmacy in Germany odds ratio (OR) 2.75 [95% confidence interval (CI) 1.73–4.37]; P < 0.001, reference group UK, the Netherlands [OR 1.91 (95% CI 1.32–2.76); P = 0.001] and Italy [OR 1.57 (95% CI 1.15–2.15); P = 0.004]. People in Poland experienced the least hyperpolypharmacy [OR 0.39 (95% CI 0.17–0.87); P = 0.021]. Conclusions: Hyperpolypharmacy is common among older people with advanced CKD, with significant international differences in the number of medications prescribed. Practice variation may represent a lack of consensus regarding appropriate prescribing for this high-risk group for whom pharmacological treatment has great potential for harm as well as benefit.